Still a superwoman? How female academics from the former Soviet Union negotiate work-family balance abroad - Antoshchuk, Irina A; Gevinner, Irina (Monitoring Obshchestvennogo Mneniya: Ekonomicheskie i Sotsial'nye Peremeny, 2020)
Since the 1930s, a peculiar 'working mother' gender contract was dominant in the Soviet Union formally empowering women. The pressing expectation of this contract and a necessity to combine motherhood, housework and employment led to the image of the near superwoman who 'has it all'. This paper examines whether highly-skilled Russian-speaking female academics continue to adhere to this cultural ideal striving for work-life balance after migration to the UK and Germany. Based on qualitative interviews with 22 female scholars, the article provides a typology of scenarios for negotiating professional and private life. It elaborates on how role-related partners contribute to achieving balance between paid employment and mothering and explores the consequences for women's well-being. Moreover, the study suggests a feminist approach to analyzing work-family balance, which valorises women's point of view, emphasizing motherhood, children and family relations as an essential personal and social value, while also documenting the increasing challenges faced in the realization of these life priorities. © 2020 Russian Public Opinion Research Center, VCIOM. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; allemagne; asie; charge mentale; conciliation famille-travail; discipline; europe; ex-URSS; famille; femmes* russophones; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; russie; régions géographiques; sciences humaines; sociologie; thématiques; travail

Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis